1987
DOI: 10.1042/bj2410265
|View full text |Cite
|
Sign up to set email alerts
|

The propeptide Asn1–Tyr126 is the storage form of rat atrial natriuretic factor

Abstract: Granules from rat atria were isolated by differential centrifugation and by a 53% (v/v) Percoll gradient after tissue homogenization in 0.25 M-sucrose/50 mM-Na2EDTA. About 40% of the immunoreactive ANF (atrial natriuretic factor) sedimented with the atrial granules during differential centrifugations. On the Percoll gradient, two distinct bands were observed. Cell debris, mitochondria, lysosomes, myofilaments and microsomes were mostly contained in the lightest-density (rho) (1.03-1.07 g/ml) fraction, as demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(61 citation statements)
references
References 32 publications
2
59
0
Order By: Relevance
“…900 of controversy when the first amino-acid sequences of CDD/ANP from extracted cardiac polypeptides were published in 1983(see review FoRSSMANN, 1986. Extraction studies indicated that the entire prohormone is probably stored in the secretory granules of myoendocrine cells (FORSSMANN et al, 1984), as confirmed by other researchers (BLOCH et al, 1985;NOKIHARA et al, 1987;THIBAULT et al, 1987;ZISFEIN et al, 1987;HASSALL et al, 1988). It is now well accepted that the prohormone of CDD/ANP contains 126 amino acids; minor quantities of smaller molecules occur in fresh endocrine heart tissue and the release of CDD/ANP is followed by the immediate formation of CDD-99-126 (SHIELDS and GLEMBOTSKI, 1988), the circulating, biologically active cardiac hormone K.…”
Section: Secretory Apparatus and Secretion Cyclesupporting
confidence: 63%
“…900 of controversy when the first amino-acid sequences of CDD/ANP from extracted cardiac polypeptides were published in 1983(see review FoRSSMANN, 1986. Extraction studies indicated that the entire prohormone is probably stored in the secretory granules of myoendocrine cells (FORSSMANN et al, 1984), as confirmed by other researchers (BLOCH et al, 1985;NOKIHARA et al, 1987;THIBAULT et al, 1987;ZISFEIN et al, 1987;HASSALL et al, 1988). It is now well accepted that the prohormone of CDD/ANP contains 126 amino acids; minor quantities of smaller molecules occur in fresh endocrine heart tissue and the release of CDD/ANP is followed by the immediate formation of CDD-99-126 (SHIELDS and GLEMBOTSKI, 1988), the circulating, biologically active cardiac hormone K.…”
Section: Secretory Apparatus and Secretion Cyclesupporting
confidence: 63%
“…Both atrial natriuretic peptide (ANP) and B‐type natriuretic peptide (BNP) are synthesized as high‐molecular weight precursors (prohormones), which are cleaved into 2 segments21, 22; 1 biologically active peptide in the C‐terminal region described as ANP or BNP, and 1 biologically inactive N‐terminal segment described as NT‐proANP or NT‐proBNP 1, 21, 22, 23. NT‐proANP is further cleaved into 3 segments; proANP 1‐30, 31‐67, and 68‐98 24.…”
mentioning
confidence: 99%
“…These membranes were separated from granules as a low density band in a Percoll gradient as described previously. 3 The preparation consisted mainly of broken cell membranes, microsomes, mitochondria, and lysosomes with very few granules.…”
Section: Isolation Of Other Membranesmentioning
confidence: 99%
“…Granules were isolated essentially as reported earlier. 3 Batches of 30 atria (from 15 rats) were processed and pooled. They were rinsed, minced, and homogenized in 0.25 M sucrose, 10 mM tris (hydroxymethyl) aminomethane (Tris) (pH 7.4), and 50 mM ethylenediamine-tetraacetic acid (EDTA) (2 atria/ml).…”
Section: Granule Isolationmentioning
confidence: 99%